Komparasi Ayam Broiler Sistem Kandang Terbuka dan Tertutup di Kabupaten OKU Timur - Adhar, Zainul; mahidin fahmie; Dicha Cahyo Komrija (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2025)
This study aims 1) To find out how much broiler chicken farm income uses a different cage system. 2) To find out the level of ratio of broiler chicken income that uses a different cage system. The results showed that the average production cost in the closed cage broiler chicken business in Buay Madang and Buay Madang Timur 2024 was Rp. 55,695,857/process, while the average production cost in the open cage broiler chicken business is Rp. 42,022,725/process. The average revenue in the closed cage broiler chicken business in Buay Madang and Buay Madang Timur 2024 is Rp. 67,218,333, while the average revenue in the open cage broiler chicken business is Rp. 45,756,667. The average revenue earned from the closed cage broiler chicken business in Buay Madang and Buay Madang Timur 2024 is 11,522,476/process while for the Broiler Chicken Broiler Open Cage business of 3,733,941/process. 95% confidence and an error rate of 5% (α = 0.05) obtained the value of t-hit = 12,573 and the value of t-table = 2,776 Thus the value of T-hit> T-table, which means that there is a significant (real) difference between the business income of the Broiler Cage Chickens closed with operating incomeBroiler chickens are open cages in Buay Madang and Buay Madang Timur. Keywords: Comparison of Broiler Chicken Revenues that use a different cage system (open and closed)